2013
DOI: 10.1002/ppp.1792
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution, Thermal Characteristics and Dynamics of Permafrost in Tröllaskagi, Northern Iceland, as Inferred from the Distribution of Rock Glaciers and Ice‐Cored Moraines

Abstract: Knowledge of the characteristics and spatial distribution of permafrost in Iceland is important to understanding slope stability, climate change impacts and palaeo‐glaciology. The permafrost distribution there, however, is poorly constrained. The presence of rock glaciers and stable ice‐cored moraines in mountain settings relates to permafrost, making such landforms indicators of present or past permafrost. This study combines recently published aerial photographs (2002–07), radar interferometry based on Advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 76 publications
7
52
0
Order By: Relevance
“…This permafrost model shows the extensive and almost continuous presence of permafrost in the Trolläskagi Peninsula, with a limit at around 800-900 m. Lilleøren et al (2013) confirm the existence of permafrost currently above 800 m a.s.l. at certain inland locations in Tröllaskagi.…”
Section: The Dynamic Of Debris-covered Glaciers and Rock Glaciers In mentioning
confidence: 50%
See 2 more Smart Citations
“…This permafrost model shows the extensive and almost continuous presence of permafrost in the Trolläskagi Peninsula, with a limit at around 800-900 m. Lilleøren et al (2013) confirm the existence of permafrost currently above 800 m a.s.l. at certain inland locations in Tröllaskagi.…”
Section: The Dynamic Of Debris-covered Glaciers and Rock Glaciers In mentioning
confidence: 50%
“…Ages of the erratic and fossil rock glacier boulders are indicated, according to Palacios et al (2015Palacios et al ( , 2016. Lilleøren et al (2013) identified 265 landforms related to the presence of permafrost in Tröllaskagi, of which 178 are rock glaciers and 87 debris-covered glaciers. The Nautárdalur is the only rock glacier which has been monitored in Tröllaskagi (Martin and Whalley, 1987;Martin et al, 1991;Whalley and Martin, 1994;Hamilton and Whalley, 1995).…”
Section: The Dynamic Of Debris-covered Glaciers and Rock Glaciers In mentioning
confidence: 99%
See 1 more Smart Citation
“…These so-called push moraines are very common at the cold glacier margins in permafrost environments (Etzelmüller and Hagen, 2005;Matthews et al, 2014;Dusik et al, 2015). As it currently occurs in the study sites (Figures 6B, 7), differential flow and ablation induce the progressive disconnection between rock glaciers and the upslope glacier zones in negative mass balance periods (Ackert, 1998;Ribolini et al, 2010;Lilleøren et al, 2013). The internal structure to the North of Tsarmine illustrates this situation: a lens of sedimentary ice (distal zone of Tsa-4; Figure 5) may have been recently integrated into the distal former frozen sediments (Tsa-3).…”
Section: Genesis and Evolutionmentioning
confidence: 99%
“…Ablation rate is then significantly reduced in these environments when the thickness of the debris cover is close to that of the permafrost active layer (i.e. seasonally thawing layer; Lilleøren and others, 2013). At the glacier margins, the deposition of the large amount of debris may induce the build-up of moraine dams (Benn and others, 2003;Iturrizaga, 2013).…”
Section: Introductionmentioning
confidence: 99%